2016
DOI: 10.1177/1932296816646798
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Educators’ Intended and Reported Use of Common Diabetes-Related Technologies

Abstract: Discrepancies and dissonance appear between diabetes educators' intentions and behavior (intentions to use and reported technology use). Intentions were higher than current use, which was relatively low and not likely to provide significant support to people with type 1 diabetes for disease management, communication, and engagement with health care services. Continuing education and experiential learning may be key in supporting diabetes educators to align their intentions with their practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(93 citation statements)
references
References 43 publications
2
90
0
1
Order By: Relevance
“…They mesh with findings from the anonymous web-based survey from which the sample derived (published elsewhere 6 ), which highlighted the need for DEs' ongoing education to promote technology adoption. Though the support need around skills may lessen in the future with the generational ages of participants predominantly not indicative of "digital natives," 31 in the meantime organizational and managerial support in the form of funding and time allowance (both study time to gain the skills and time to use them) would assist, as would rotating placements across and between pediatric and adult diabetes care settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They mesh with findings from the anonymous web-based survey from which the sample derived (published elsewhere 6 ), which highlighted the need for DEs' ongoing education to promote technology adoption. Though the support need around skills may lessen in the future with the generational ages of participants predominantly not indicative of "digital natives," 31 in the meantime organizational and managerial support in the form of funding and time allowance (both study time to gain the skills and time to use them) would assist, as would rotating placements across and between pediatric and adult diabetes care settings.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 213 members who responded to advertisements in the ADEA newsletter and completed an anonymous webbased survey (published elsewhere 6 ) were supplied with study information and invited to participate; interested participants provided their contact details. Interviews were conducted by the first author, whose professional standing as a DE facilitated development of the trust necessary to share private, sensitive, or controversial details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Storni [43] found that patient generated tags for mobile devices developed by participants were not of interest to clinicians who were more focused on numerical values. James et al [48] has explored the perceptions and experiences of diabetes educators when supporting the use of advanced technology and suggests that there are challenges for all parties. This includes device costs, access to WIFI and appropriate mobile devices.…”
Section: Implications For Healthcare Practicementioning
confidence: 99%